Persepsi Mahasiswa Terhadap Pelayanan Akademik oleh Tenaga Kependidikan pada Fakultas Ilmu Pendidikan Universitas Negeri Padang - Nurhaliza; Nelfia Adi (Journal of Practice Learning and Educational Development, 2024)
The purpose of this study is to ascertain and evaluate how State University of Padang's Faculty of Education's students feel about academic services. This research employs a quantitative descriptive methodology. There were 1168 students in the study's population, and 308 students were selected at random using the Proportional Random Sampling approach, with the sample size calculated using the Slovin formula at a 5% error rate. The data analysis's conclusions demonstrate how students view the academic services provided by FIP UNP's education staff from the following perspectives: 1) tangible, with an average score of 3.99; 2) reliable, with an average score of 3.90; 3) responsive, with an average score of 3.84; 4) assured, with an average score of 3.93; and 5) emphatic, with an average score of 3.48. Overall, students' perceptions of the academic services provided by FIP UNP educators fall into the good category, with an average score of 3.83.